2012
DOI: 10.1590/s1517-83822012000100048
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated gastric carcinoma in Brazil: comparison between in situ hybridization and polymerase chain reaction detection

Abstract: Epstein-Barr virus (EBV) has been associated with 10% of gastric carcinomas. The aim of this study was to determine the frequency of EBV in gastric carcinomas in Brazil assessed by in situ hybridization (ISH) and PCR, which would contribute to the characterization of the clinical and pathological aspects of EBVassociated gastric carcinomas. One hundred and ninety-two gastric carcinoma cases were collected at hospitals in two Brazilian states. Seventy-three out of 151 cases were PCR(+), while 11/160 cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Regarding the pathological clinical features, both FISH and qPCR found more EBV in older men and in patients in a more advanced stage of cancer, reproducing the findings obtained by many authors around the world [ 4 , 20 , 21 ]. In addition, the distal region and intestinal type were the most affected.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the pathological clinical features, both FISH and qPCR found more EBV in older men and in patients in a more advanced stage of cancer, reproducing the findings obtained by many authors around the world [ 4 , 20 , 21 ]. In addition, the distal region and intestinal type were the most affected.…”
Section: Discussionsupporting
confidence: 87%
“…It is also possible to explain this difference with polymorphism that could occur in viral genome sequencing [23]. The presence of the virus was verified in 36 of the 186 cases by Karpiniski et al [35].…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that EBV is associated with 10% of gastric carcinomas and that in most cases positive EBV is diagnosed in poorly differentiated or moderately differentiated grades [23,24]. The progress of any malignancy associated with EBV requires the establishment of complex cell interactions in epithelial cells and specific viral gene expression.…”
Section: Discussionmentioning
confidence: 99%